ANALISIS PENERIMAAN DAN PENGGUNAAN APLIKASI SiKerja : Di Lingkungan Kementerian Dalam Negeri Menggunakan Pendekatan Technology Acceptance Model (TAM) - Gilang Priambodo; Theresiawati Theresiawati; Rio Wirawan (Universitas Mercu Buana, 2022)
AbstracThe purpose of this study was to determine the level of acceptance and users of the use of the SiKerja application within the Ministry of Internal Affairs by using the Technology Acceptance Model method approach. which uses five variables, namely perceived ease of use, perceived usefulness, attitude toward using, behavioral intention to use and actual system use. The type of data used is primary data obtained from questionnaires. The number of samples was 150 employees, then the data obtained were analyzed using the Structured Equation Model-Partial Least Square (SEM-PLS) method using smartPLS software. The results showed that there were 3 out of 5 hypotheses that had a significant positive effect, namely the variable perceived ease of use on perceived usefulness with a path coefficient value of 0.69 and a t- statistics value of 2.12, a variable perceived usefulness on behavioral intention to use with a path coefficient value of 0.75 and a t-value. statistics 2.12, the perceived usefulness variable towards Attitude toward using with a path coefficient value of 0.60 and a t-statistic value of 2.15. However, there are also 2 variables that do not have a significant effect, namely, perceived ease of use on attitude toward using with a path coefficient value of 0.61 and a t- statistic value of 1.04 and a perceived usefulness variable on actual system use with a path coefficient value of 0.60 and a t-statistic value of 1.02. .Keywords: SiKerja, Technology Acceptance Model (TAM), Structured Equation Model (SEM), Partial Least Square (PLS).